BANK CREDIT: ROLE IN THE INDIAN INDUSTRIAL SECTOR - Singh, Naib (International Journal For Research In Business, Management And Accounting, 2017)
The main finding of this paper highlights that the gross bank credit to the Indian industrial sector has been increased year by year at the rapid speed. Industries need credit facilities for the various types of functions like production, purchasing of material, marketing and payment to the workforce. In 2010 the industrial credit of Rs. 13114.52 billion was outstanding which has increased up to Rs. 26576.27 billion in the year 2015. It has increased up to two times in just five years. The importance of bank credit cannot be ignored in the present scenario.